Characterization of embryonic globin genes of the zebrafish. - Brownlie, A; Hersey, C; Oates, A; Paw, B; Falick, A; Witkowska, H; Flint, J; Higgs, D; Jessen, J; Bahary, N; Zhu, H; Lin, S; et al. (2003)
Hemoglobin switching is a complex process by which distinct globin chains are produced during stages of development. In an effort to characterize the process of hemoglobin switching in the zebrafish model system, we have isolated and characterized several embryonic globin genes. The embryonic and adult globin genes are found in clusters in a head-to-head configuration. One cluster of embryonic and adult genes is localized to linkage group 3, whereas another embryonic cluster is localized on linkage group 12. Several embryonic globin genes demonstrate an erythroid-specific pattern of expression early during embryogenesis and later are downregulated as definitive hematopoiesis occurs. We utilized electrospray mass spectroscopy to correlate globin genes and protein expression in developing embryonic red cells. The mutation, zinfandel, has a hypochromic microcytic anemia as an embryo, but later recovers in adulthood. The zinfandel gene maps to linkage group 3 near the major globin gene locus, strongly suggesting that zinfandel represents an embryonic globin defect. Our studies are the first to systematically evaluate the embryonic globins in the zebrafish and will ultimately be useful in evaluating zebrafish mutants with defects in hemoglobin production and switching.